2007
DOI: 10.1902/jop.2007.060325
|View full text |Cite
|
Sign up to set email alerts
|

Acellular Dermal Matrix as a Membrane for Guided Tissue Regeneration in the Treatment of Class II Furcation Lesions: A Histometric and Clinical Study in Dogs

Abstract: The ADM demonstrated histomorphometric results similar to the bioabsorbable membrane and resulted in a greater increase in the thickness of the keratinized tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 42 publications
2
31
0
2
Order By: Relevance
“…In similar defects, Andrade, et al 1 (2007) observed a correlation between the exposure of the membrane and the epithelial migration. The presence of epithelial tissue was observed in all histological sections of the sites that shown a membrane exposure and was ascribed to the degradation of the exposed portions of this material.…”
Section: Discussionmentioning
confidence: 87%
“…In similar defects, Andrade, et al 1 (2007) observed a correlation between the exposure of the membrane and the epithelial migration. The presence of epithelial tissue was observed in all histological sections of the sites that shown a membrane exposure and was ascribed to the degradation of the exposed portions of this material.…”
Section: Discussionmentioning
confidence: 87%
“…After carefully removing the anesthesia needle, the penetration depth was measured with a caliper with a 0.05‐mm resolution 18 . The clinical measurements of WKT and TKT were performed three times by the same examiner (DMR), and the mean from these three values was calculated to represent WKT and TKT, respectively 18,34 . The time between the measurements was ≈10 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Histological and clinical studies have reported the potential of guided tissue regeneration (GTR) to regenerate periodontal ligament, cementum and alveolar bone (2,3), and the technical reasons for the success of this technique are well described in literature (4). In GTR, a barrier is inserted between the root surface and the gingival tissues to inhibit the apical migration of the epithelium and gingival connective tissue of the flap, allowing the granulation tissue derived from the periodontal ligament and osseous tissues to repopulate the space adjacent to the denuded root surface.…”
Section: Introductionmentioning
confidence: 99%